PLC Outseal Training for PVTE Students at Sultan Ageng Tirtayasa University: Pelatihan PLC Outseal Bagi Mahasiswa PVTE Universitas Sultan Ageng Tirtayasa - Bagus Dwi Cahyono; Irwanto Irwanto (Yayasan Ahmar Cendekia Indonesia, 2023)
Programmable Logic Controller is a device that can be programmed according to the needs of industrial processes. This activity is a service activity for lecturers of the PVTE Study Program at Sultan Ageng Tirtayasa University which is expected to be able to improve student skills in terms of becoming provisions in the world of work. This PLC Outseal Training activity is carried out face-to-face for 8 hours in the FKIP educational room at Sultan Ageng Tirtayasa University. The training method uses a practical based method. Includes material: Introduction to HMI and SCADA; Advanced PLC programming with Outseal PLC hardware; and PLC connection with upper layer. The evaluation results showed that students seemed interested and did not experience any problems when practicing PLC. Abstrak Programmable Logic Controller merupakan suatu perangkat yang mampu diprogram sesuai kebutuhan proses industri. Kegiatan ini sebagai kegiatan pengabdian dosen Prodi PVTE Universitas sultan ageng tirtayasa yang diharapkan mampu meningkatkan keterampilan mahasiswa dalam hal menjadi bekal dalam dunia kerja. Kegiatan Pelatihan PLC Outseal ini dengan dilakukan secara tatap muka selama 8 jam di ruang edutaria FKIP Universitas sultan ageng tirtayasa. Adapun metode pelatihan ini menggunakan metode practical based methode. Meliputi materi: Pengenalan HMI dan SCADA; Programing lanjut PLC dengan hardware Outseal PLC; dan Koneksi PLC dengan upper layer. Hasil evaluasi menunjukkan bahwa mahasiswa terlihat tertarik dan tidk mengalami kendaa saat praktik PLC.